Identificação e caracterização de ATPase de gavinha de Passiflora sp - Gouveia, Edilge Maria de (2000)
Tendrils are highly dynamic structures, whose spiraling movement is dependent on ATP, which suggests the involvement of ATPases in this process. In this work, our objective was to isolate ATPase from the tendril of Passiflora sp. The tendrils of Passiflora sp were homogenized in 50mM pfl 8.5 Imidazole buffer containing protease inhibitors (EDTA and PMSF) and centrifuged at 40,000g for 40 minutes. After adjusting the pH of the supernatant fraction to 4.5, it was treated with ammonium sulfate and the supernatant fraction 40% ammonium sulfate was dialyzed and subjected to enzymatic characterization. This fraction showed both Ca - ATPásica and Mg - ATPásica activity, the first being 60% higher than the second, however in the presence of Ca and Mg the activities were not added, suggesting that they are not distinct ATPases. Mg - ATPase activity was inhibited by about 30% in the presence of high ionic strength (0.3 M NaCl and 0.3 M KCl). The aluminum fluoride did not inhibit the Mg - ATPásica activity of the soluble fraction, however the fluoride ion inhibited about 33% of the Mg - ATPásica activity. The Mg - ATPásica activity showed an increasing reduction in the presence of vanadate in concentrations of 50, 200 and 100,000 m, with respectively 32, 61 and 78% reduction. The lmM azide and triton X 100 practically did not alter activity suggesting, respectively, that F1 ATPase and dinein are not present in this preparation. The absence of K / EDTA - ATPase activity suggests that myosin is also not present in our preparation. Dialysis of the ATPase fraction causes a significant reduction in its Mg - ATPase activity, this activity was restored when the dialysed soluble fraction was incubated with the boiled soluble fraction. Our ATPase fraction was centrifuged and applied to a Q - Sepharose column. The column was washed with 0.2M NaCl and subsequently, ATPase activity was eluted with 0.5M NaCl. The main polypeptide observed in this fraction, through SDS - PAGE, has a relative mobility of approximately 29 KDa. The Mg-ATPasic activity of this fraction is stimulated by the boiled soluble fraction. Thus we obtain, in this work, an ATPase of soluble fraction of the tendril of Passiflora sp that is stimulated by an endogenous thermostable factor.